Pengaruh Job Crafting Terhadap Work Engagement Melalui Mindfulness Sebagai Mediator - Siti Aisyah (Publikasi Indonesia, 2022)
Companies or organizations seek to optimize human resources in the face of competition. One of the HR functions in a company is to create work engagement or work engagement for its employees. One of the factors that can affect work engagement in a company is job crafting. This study aims to determine and analyze the effect of job crafting on work engagement through mindfulness as a mediator for employees of PT. X Surabaya. This research is a causality study using a quantitative approach. The number of samples is 50 employees. Statistical analysis using Partial Least Square (PLS) with the help of SmartPLS 3.0 software. The results of this study explain that job crafting has a significant effect on work engagement. Job crating also has a significant effect on mindfulness. Mindfulness has been shown to have no significant effect on work engagement. The role of mindfulness mediator has no significant effect between job crafting and work engagement. The managerial implication of the results of this study is that PT. X Surabaya can improve job crafting for its employees so that employees have high work engagement and mindfulness.